Privacy Enhancing Technologies implementation: An investigation of its impact on work processes and employee perception. (May 2019) - Gan, May Fen; Chua, Hui Na; Wong, Siew Fan
Highlights: This paper examines the effect of the PETs implementation on employees' work processes and their perception toward the implementation. Interview data shows that the PETs affected the workload, communication loads, and data access depending on the nature of the work. The employees perceived the PETs as useful. The employees raised concerned on vendors' accountability and the sustainability of the PETs. Abstract: With increasing consumer awareness towards information privacy and government-enforced regulations on data protection, organizations are implementing Privacy Enhancing Technologies (PETs) to provide systematic protection on consumers' personal data. Current PETs literature focused mostly on the design and implementation of the technology without touching on its impact. Implementation literature has also examined the effects of various technologies on changes in work processes and employee perception but has yet to explore that of PETs. Therefore, the objective of this study is to understand the effects of PETs implementation on employees' work processes as well as their perception towards the implementation. In-depth interview data was collected from three groups of affected employees belonging to one large mobile telecommunications company. Results show that PETs affected workload, communication level and data access, which led to different levels of changes depending on the nature of the work. The employees perceived PETs as useful. However, they perceived the company as not being properly prepared for the implementation, and also raised concerns on vendor accountability and the sustainability of the PETs. Our findings have implications for organizations planning to implement PETs.